Lightning strike resistance of an electrically conductive CFRP with a CSA-doped PANI/epoxy matrix. (1st December 2017) - Katunin, Andrzej; Krukiewicz, Katarzyna; Turczyn, Roman; Sul, Przemysław; Dragan, Krzysztof
Abstract: An analysis of a structural damage extent of a developed electrically conductive CFRP composite exposed to the high-current electrical discharges simulating lightning strikes was conducted in order to evaluate its ability of carrying on lightning electrical current and its damage resistance during lightning events. The composite was fully fabricated from organic compounds, i.e. electrically conductive polymer blend of polyaniline (PANI) doped with camphorsulfonic acid (CSA) and epoxy resin, and carbon fabric used both as a mechanical reinforcement as well as supporting electrical conductor for ensuring adequate electrical conductivity and mechanical properties. An investigation of lightning strike resistance was performed during high-voltage and high-current mode tests. For preliminary evaluation the resulting damage was examined using visual inspection. Furthermore, the ultrasonic testing and X-ray computed tomography were applied for evaluation of degradation mechanisms occurring during a typical lightning strike event. The obtained results show that the developed composite is characterized by good electrical conductivity and mechanical properties and may successfully resist high-current impulse discharges typical for lightning strike events. Therefore, the developed composite can be considered as a potential candidate for a lightning strike protection material in aircraft industry and other applications.